Finding jobs in private households online: A comparative analysis of digitally-mediated care and domestic service work in Australia, Germany, Denmark, Spain and the United Kingdom - Friederike Molitor; Stefan Munnes; Piotr Wójcik; Lena Hipp (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
We study the working conditions of care and domestic workers who offer their services on digital platforms in Australia, Germany, Denmark, Spain and the United Kingdom. By drawing on survey data collected on a digital platform in 2019, we examine workers' demographics and their experiences with the online platform and with their clients.
Keywords: 330; Care and domestic service work; platform economy; gender